Being the best: Attitudes and motivation amongst the World’s leading golfers - Mansfield, Roger (2012)
What does it take to be the best in the World in a given activity? This study examines the attitude and motivation of the World's best golfers in contrast to other golfers who hadn't made the jump to fame. A total of 63 golfers were interviewed using the same interview script. The World Nº1 Men, Senior Men and Women were part of the sample. Much as will be the case with most professions, being able to work exceedingly long hours over a long period of time i.e. decades seems to be a pre-requisite for success on a Worldwide scale.